2013
DOI: 10.1167/13.5.23
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of dynamic and static facial expression recognition

Abstract: Unlike frozen snapshots of facial expressions that we often see in photographs, natural facial expressions are dynamic events that unfold in a particular fashion over time. But how important are the temporal properties of expressions for our ability to reliably extract information about a person's emotional state? We addressed this question experimentally by gauging human performance in recognizing facial expressions with varying temporal properties relative to that of a statistically optimal ("ideal") observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
64
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(72 citation statements)
references
References 27 publications
7
64
1
Order By: Relevance
“…The lack of consistency across studies may also result from the nature of the stimulus materials used. Although some studies have used stimuli based on real human models (actors or nonactors), others included avatars or computer edited faces (e.g., Cigna et al, 2015;Gold et al, 2013;Horstmann & Ansorge, 2009). Yet some authors (e.g., Sato, Fujimura, & Suzuki, 2008) suggest that the use of Breal people^is more suitable when using dynamic stimuli.…”
Section: Static Versus Dynamic Facial Expressionsmentioning
confidence: 99%
“…The lack of consistency across studies may also result from the nature of the stimulus materials used. Although some studies have used stimuli based on real human models (actors or nonactors), others included avatars or computer edited faces (e.g., Cigna et al, 2015;Gold et al, 2013;Horstmann & Ansorge, 2009). Yet some authors (e.g., Sato, Fujimura, & Suzuki, 2008) suggest that the use of Breal people^is more suitable when using dynamic stimuli.…”
Section: Static Versus Dynamic Facial Expressionsmentioning
confidence: 99%
“…Thirdly, although we utilised a dynamic emotional expression task to increase the ecological validity of the task, some studies have suggested that the dynamic facial movements actually play only a small role in the ability to identify emotion from facial expressions (Gold et al, 2013). Nonetheless, employing different variants of facial emotion stimuli develops our understanding of the robustness or otherwise of any effect irrespective of an impact on ecological validity.…”
mentioning
confidence: 99%
“…In addition, it would also be interesting to clarify whether deaf adults would benefit from the presentation of dynamic emotional expressions over static images. We very recently showed that the performance for the recognition of static as compared to dynamic expressions was notably less effective in fragile face processing systems, such as brain-damaged patients (Richoz, Jack, Garrod, Schyns, & Caldara, 2015) and elderly adults (Richoz, Lao, Pascalis, & Caldara, 2018) by using a database of stimuli controlled for the amount of low-level information carried over time (Gold et al, 2013). As sign language is dynamic, we could expect similar results in the deaf population, a question that needs to be addressed in a future study.…”
Section: Discussionmentioning
confidence: 81%